PENATALAKSANAAN FISIOTERAPI PADA KASUS ASMA UNTUK MENINGKATKAN VO2MAX DENGAN MENGGUNAKAN MODALITAS ACBT DAN SENAM ASMA - Erinta Ningrum; Maulida Wijaya Putri; Yulisha Eva Oktaviani (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2025)
Asthma is a condition involving chronic inflammation of the airways, which leads to narrowing of the air passages (bronchial hyperreactivity). This results in decreased metabolism and energy, causing dysfunction. Moreover, the gas exchange of O2 and CO2 is reduced, leading to a lower VO2Max and causing shortness of breath. This study aims to examine the impact of Active Cycle of Breathing Technique (ACBT) exercises and Asthma Gymnastics on improving VO2Max in asthma patients, using the Six Minute Walking Test (6MWT) as the research instrument. The study included two participants aged 19 years (66.6%) and one participant aged 21 years (33.4%). The findings indicated an improvement in VO2Max after applying ACBT and Asthma Gymnastics. Ms. S showed an increase in VO2Max from 24.0 (poor) to 26.4 (poor); Ms. D improved from 19.5 (very poor) to 21.9 (very poor); and Ms. A improved from 17.9 (very poor) to 20.6 (very poor).